2019
DOI: 10.15678/ier.2019.0504.09
|View full text |Cite
|
Sign up to set email alerts
|

Okun’s law in an emerging country: An empirical analysis in Indonesia

Abstract: Labor economics policy instruments, such as gross domestic product (GDP) and unemployment are persistent challenges for every country. As an emerging country, Indonesia seeks to reduce unemployment and increase gross domestic product. The aim of this study is to investigate the relationship between GDP and the open unemployment rate in Indonesia starting from 1987 to 2017. Research Design & Methods: The data were obtained from Indonesia's Central Bureau of Statistics website. Moreover, the econometric model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It was common in developing countries such as Indonesia to be capital intensive (Lee & Huruta, 2019). Employers in developing countries were high profit-oriented by using existing technologies and reducing the number of employees they needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was common in developing countries such as Indonesia to be capital intensive (Lee & Huruta, 2019). Employers in developing countries were high profit-oriented by using existing technologies and reducing the number of employees they needed.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Lee and Huruta (2019) find that the open unemployment rate does Granger cause gross domestic product, but not vice versa. In line with the Structural Vector Auto-regression, there is a negative relationship between GDP and the open unemployment rate.…”
Section: Literature Reviewmentioning
confidence: 96%
“…change in the unemployment rate. By many researchers, the above relationship with the confidence interval taken into account has been empirically confirmed on the example of other economies (Lee & Huruta, 2019), sometimes examining the above relationship with extended vector-autoregression models (Pata et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…In Eastern European Countries, Soylu et al (2018) investigated the relationship between economic growth and unemployment and found that economic growth positively affects unemployment. In Indonesia, Lee and Huruta (2019) use the Granger causality test to suggest that the open unemployment rate causes Granger in the GDP, but not vice versa. Consistent with structural vector autoregression, a negative relationship existed between GDP and the open unemployment rate.…”
Section: Economic Growth and Inflation In Africamentioning
confidence: 99%